2009
DOI: 10.1152/ajpheart.01298.2008
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of 5′-AMP-activated protein kinase activity does not impair recovery of contractile function during reperfusion of ischemic hearts

Abstract: Folmes CD, Wagg CS, Shen M, Clanachan AS, Tian R, Lopaschuk GD. Suppression of 5Ј-AMP-activated protein kinase activity does not impair recovery of contractile function during reperfusion of ischemic hearts. Am J Physiol Heart Circ Physiol 297: H313-H321, 2009. First published May 8, 2009 doi:10.1152/ajpheart.01298.2008.-Activation of 5Ј-AMP-activated protein kinase (AMPK) may benefit the heart during ischemia-reperfusion by increasing energy production. While AMPK stimulates glycolysis, mitochondrial oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…In hearts from AMPK dominate negative mutant of the α2 subunit (DNα2) of mice showed an actual increase in cardiac functional recovery during reperfusion after ischemia (Lopaschuk, 2008). Moreover, suppression of cardiac AMPK activity did not affect baseline cardiac function but may in fact improve the recovery of cardiac function after ischemia (Folmes et al, 2009). These seemingly controversial results may due to AMPK activation during ischemia not only has the potential to increase glucose uptake and glycolysis promoting energy supply to the heart but also has the potential to increase fatty acid oxidation, which by suppressing glucose oxidation can increase proton production and decrease cardiac function (Lopaschuk, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In hearts from AMPK dominate negative mutant of the α2 subunit (DNα2) of mice showed an actual increase in cardiac functional recovery during reperfusion after ischemia (Lopaschuk, 2008). Moreover, suppression of cardiac AMPK activity did not affect baseline cardiac function but may in fact improve the recovery of cardiac function after ischemia (Folmes et al, 2009). These seemingly controversial results may due to AMPK activation during ischemia not only has the potential to increase glucose uptake and glycolysis promoting energy supply to the heart but also has the potential to increase fatty acid oxidation, which by suppressing glucose oxidation can increase proton production and decrease cardiac function (Lopaschuk, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…125, 126 However, not all studies have documented a protective function of the AMPK pathway during ischemia. 127 …”
Section: Ampk Action During Myocardial Ischemia-reperfusionmentioning
confidence: 99%
“…In the ischemic heart the effect of AMPK activation is reported to be beneficial by preventing post-ischemic cardiac dysfunction, apoptosis, and injury [3], [4], [5], [6]. These studies, however, have been contradicted by others, which showed that activation of AMPK in the ischemic heart has either no effect [7] or increases apoptosis [8]. Contrasting with the heart, activation of AMPK in the ischemic brain appears to worsen injury [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%